2013
DOI: 10.1080/02626667.2012.755264
|View full text |Cite
|
Sign up to set email alerts
|

A neuro-fuzzy-based modelling approach for sediment transport computation

Abstract: The application of a data-driven adaptive neuro-fuzzy modelling technique for predicting bed load and total bed-material load for the River Rhine is summarized. Four main parameters affecting sediment transport are used to construct the model, using 560 and 510 measured bed load and total bed-material load data, respectively. Two-thirds of the available data sets are used for training and one third for testing. The initial fuzzy model is obtained by grid partitioning of the input variables. The optimization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…Few outliers can dominate the MARE. The MARE not only gives the average performance index in terms of predicting flow rates but also the distribution of the prediction errors (Wieprecht et al 2013).…”
Section: Model Performance Evaluationmentioning
confidence: 99%
“…Few outliers can dominate the MARE. The MARE not only gives the average performance index in terms of predicting flow rates but also the distribution of the prediction errors (Wieprecht et al 2013).…”
Section: Model Performance Evaluationmentioning
confidence: 99%
“…These ANN predictions are often tested against domain models and theories. Tayfur, 2002;Lin and Montazeri Namin, 2005;Bhattacharya et al, 2007;Yang et al, 2009 Adaptive-network-based fuzzy inference system (ANFIS) Wieprecht et al (2013) demonstrated that the ANFIS approach could be a useful alternative technique for predicting both bedload and total bed-material load. Lin and Montazeri Namin (2005) found that the method can be used to model both uniform and non-uniform suspended sediment.…”
Section: Annmentioning
confidence: 99%
“…Do sada je provedeno nekoliko istraživanja o primjeni ANFIS-a u predviđanju nanosa. U mnogim je istraživačkim radovima u tijeku dokazivanja koncepta primjene ANFIS-a utvrđeno da se taj model ponaša vrlo dobro u usporedbi s konvencionalnim modelima krivulja nanosa, te da uzima u obzir i složene nelinearne pojave [17][18][19]. Kisi i Shiri [20] usporedili su tehniku genetičkog programiranja (eng.…”
Section: Uvodunclassified